CALL E-Portfolios: Developing Reflective and Autonomous Learning - Papadima-Sophocleous, Salomi (My University, 2009)
This paper provides an overview of the work carried out over the period of a semester with a group of BA in English Language and Literature students studying CALL in a private tertiarity institution in Cyprus. It claims that by using E-Portfolios in undergraduate CALL courses, students do not only aquire theoritical knowledge and practical skills in the area of using new technologies in second language(L2) teaching and learning, but also develop reflective autonomous learning skills, which would prepare them for lifelong learning. The paper first introduces the rationale for the use of E-Portfolios with this group of students. Then it reports on their feedback, deriving from their reflections on four different aspects. Lastly, it draws some preliminary conclusions that suggest how students' reflections contribute to a greater student involvment in the learning process, and to more autonomous CALL learners and future practitioners.
Keywords: E-Portfolios; CALL; Second Language